2020
DOI: 10.1371/journal.pone.0235232
|View full text |Cite
|
Sign up to set email alerts
|

Delayed short-term tamoxifen treatment does not promote remyelination or neuron sparing after spinal cord injury

Abstract: The tamoxifen-dependent Cre/lox system in transgenic mice has become an important research tool across all scientific disciplines for manipulating gene expression in specific cell types. In these mouse models, Cre-recombination is not induced until tamoxifen is administered, which allows researchers to have temporal control of genetic modifications. Interestingly, tamoxifen has been identified as a potential therapy for spinal cord injury (SCI) and traumatic brain injury patients due to its neuroprotective pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 88 publications
(150 reference statements)
0
8
0
Order By: Relevance
“…Only one study showed that estrogen did not affect the lesion size using hematoxylin and eosin staining, however they noted that their protocol was unlikely to be sensitive enough to detect changes in lesion size in their moderate SCI lesion model (Letaif et al, 2015). One study also found that tamoxifen had no effect on lesion size (Pukos & McTigue, 2020). This study, however, reportedly used a very high (300mg/kg) dose of tamoxifen in mice.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Only one study showed that estrogen did not affect the lesion size using hematoxylin and eosin staining, however they noted that their protocol was unlikely to be sensitive enough to detect changes in lesion size in their moderate SCI lesion model (Letaif et al, 2015). One study also found that tamoxifen had no effect on lesion size (Pukos & McTigue, 2020). This study, however, reportedly used a very high (300mg/kg) dose of tamoxifen in mice.…”
Section: Resultsmentioning
confidence: 99%
“…Two studies, however, demonstrated no effect. One study showed that estrogen (Letaif et al, 2015) and another, using a dose of tamoxifen well outside of the clinical range, showed that tamoxifen (Pukos & McTigue, 2020) had no effect on axon integrity and sparing.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…PDGFRα-CreER T2 : Tau-mGFP mice were given tamoxifen by oral gavage to induce recombination prior to SCI or at different times post-injury, then 5-ethynyl-2 0 -deoxyuridine (EdU) was dissolved in their drinking water to label proliferating cells. Although tamoxifen may be neuroprotective and can accelerate OL differentiation and remyelination in models of primary demyelination (Gonzalez et al, 2016), the tamoxifen regimen used in this report and prior studies does not change OL function or remyelination after SCI (Pukos & McTigue, 2020). One cohort of mice did not receive EdU and underwent in vivo electrophysiology recordings and behavioral testing.…”
Section: Experimental Designmentioning
confidence: 88%
“…Brains were frozen, cut at 10µm on a cryostat, and mounted. Sections were immunolabeled for Iba1 or GFAP as previously described (Invitrogen) ( 57 ). Next, three images from hypothalamus (paraventricular nucleus and lateral hypothalamic nucleus) and hippocampus (CA3 region) were collected for each brain, and the immunoreactive area of GFAP and Iba1 of each section was quantified using image analysis (Image J).…”
Section: Methodsmentioning
confidence: 99%